2003
DOI: 10.1179/000349803235002399
|View full text |Cite
|
Sign up to set email alerts
|

Human cytokine responses to meso-endemic malaria on the Pacific Coast of Colombia

Abstract: Studies of naturally-acquired immunity to malaria in endemic regions provide the potential for a greater understanding of the regulation of human immune responses to the malarial parasite. However, little is known about the acquisition of malaria-specific immunity in regions of unstable, meso-endemic or hypo-endemic transmission. Cytokine profiles - patterns in the expression of interleukin-4 (IL-4), interleukin-10, interleukin-12, interferon-gamma (IFN-gamma) and tumour necrosis factor-alpha (TNF-alpha) - wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 13 publications
(1 reference statement)
0
12
0
1
Order By: Relevance
“…In an animal study, pro‐inflammatory response was shown to be important for the early immune response and control of parasitaemia in P. cynomolgi malaria ( P. vivax ‐like malaria) (45). On the other hand, another study found more pro‐inflammatory response in P. vivax malaria than in P. falciparum malaria (46). Our findings suggest that the pro‐inflammatory response to P. vivax bears more importance during periods of increased parasitaemia.…”
Section: Discussionmentioning
confidence: 98%
“…In an animal study, pro‐inflammatory response was shown to be important for the early immune response and control of parasitaemia in P. cynomolgi malaria ( P. vivax ‐like malaria) (45). On the other hand, another study found more pro‐inflammatory response in P. vivax malaria than in P. falciparum malaria (46). Our findings suggest that the pro‐inflammatory response to P. vivax bears more importance during periods of increased parasitaemia.…”
Section: Discussionmentioning
confidence: 98%
“…51 The type 2 cytokine profile, dominated by IL-4 expression, is less frequently associated with P. vivax infection and is usually noticeable only after prolonged exposure to the parasite. 52 However, IL-10 may be elevated during Plasmodium infection to "prevent both hyper-parasitemia and host pathology." 52 That is, a strong proinflammatory cytokine response should be balanced by a strong anti-inflammatory cytokine response.…”
Section: Discussionmentioning
confidence: 99%
“…52 However, IL-10 may be elevated during Plasmodium infection to "prevent both hyper-parasitemia and host pathology." 52 That is, a strong proinflammatory cytokine response should be balanced by a strong anti-inflammatory cytokine response. 45 In the current study, various cytokine levels were significantly higher in male and female cases on day of diagnosis as compared with 8 days post-diagnosis (following chloroquine treatment) or when compared with the age-and sex-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Patients having moderate parasitemia in endemic regions of Colombia have high IFN-γ and TNF-α levels, a pro-inflammatory cytokine profile correlated with the response found in an unstable transmission region. The balance in interleukin (IL)-10/TNF-α rate could prevent increased parasitemia and host pathology ( 58 ).…”
Section: Immune Response Regarding Malariamentioning
confidence: 99%